Funktsional'noe znachenie osobennostei perifericheskoi krovi u sportsmenov s razlichnoi napravlennostyu trenirovochnogo processa - Khrebtova, A. Yu. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the functional interrelations between the peculiarities of athletes' peripheral blood, the immunity to hypoxia and the character of vegetative regulation in circulation. It had been shown that the growth of immunity to hypoxia when aerobic orientating of training process developes mainly due to increase of the functional capacities of the erythron's peripheral formation. The decrease of the athletes' organism stress-reactivity ensures the noticable input to hypoxia's immunity in athletes with the aerobic orientation of the training process.